Double‐Barrel Versus Single‐Barrel Fibula Flaps for Mandibular Reconstruction: Safety and Outcomes. (27th November 2021) - Trilles, Jorge; Chaya, Bachar F.; Daar, David A.; Anzai, Lavinia; Boczar, Daniel; Rodriguez Colon, Ricardo; Hirsch, David L.; Jacobson, Adam S.; Levine, Jamie P.
Abstract : Objectives/Hypothesis: Fibula flaps are routinely used for osseous reconstruction of head and neck defects. However, single‐barrel fibula flaps may result in a height discrepancy between native mandible and grafted bone, limiting outcomes from both an aesthetic and dental standpoint. The double‐barrel fibula flap aims to resolve this. We present our institution's outcomes comparing both flap designs. Study Design: Retrospective cohort study. Methods: We conducted a retrospective review of all patients undergoing free fibula flap mandibular reconstruction at our institution between October 2008 and October 2020. Patients were grouped based on whether they underwent single‐barrel or double‐barrel reconstruction. Postoperative outcomes data were collected and compared between groups. Differences in categorical and continuous variables were assessed using a Chi‐square test or Student's t ‐test, respectively. Results: Out of 168 patients, 126 underwent single‐barrel and 42 underwent double‐barrel reconstruction. There was no significant difference in postoperative morbidity between approaches, including total complications ( P  = .37), flap‐related complications ( P  = .62), takeback to the operating room ( P  = .75), flap salvage ( P  = .66), flap failure ( P  = .45), and mortality ( P  = .19). In addition, there was no significant difference in operative time ( P  = .86) or duration of hospital stay ( P  = .17). After adjusting for confounders, primary dental implantation was significantly higher in the double‐barrel group (odds ratio, 3.02; 95% confidence interval, 1.2–7.6; P  = .019). Conclusion: Double‐barrel fibula flap mandibular reconstruction can be performed safely without increased postoperative morbidity or duration of hospital stay relative to single‐barrel reconstruction. Moreover, the double‐barrel approach is associated with higher odds of primary dental implantation and may warrant further consideration as part of an expanded toolkit for achieving early dental rehabilitation. Level of Evidence: 3 Laryngoscope, 132:1576–1581, 2022